Assessing the Sectoral Impact of Renewable Energy Adoption on CO2 Emissions in the United States - Zor, Coolin-Campbell M.; Alade, Elvis; Yougang, Blanche Brinda; Bom, Charles (International Journal of Energy Economics and Policy, 2025)
This paper presents an assessment of renewable and fossil fuel consumption on CO₂ emissions of major polluting sectors in the United States using an Autoregressive Distributed Lag Error Correction Model (ARDL-ECM). The results show that renewable energy reduces emissions in the long-run, though short-run effects vary by sector due to integration challenges. The production and consumption of fossil fuels remain a dominant driver of emissions, particularly in the industrial, transportation, and electric power sectors. Energy prices also play a critical role: while higher electricity prices promote efficiency, elevated crude oil prices are associated with sustained emissions. Industry-specific dynamics emphasize the need for targeted policies such as investments in modernizing the grid, industrial energy efficiency and adoption of electric vehicles. While the renewable transition aligns with economic growth, ensuring equitable access and adapting the technology in the face of change is a daunting task. These results also highlight the importance of adaptive sectoral approaches that help align decarbonization objectives with economic sustainability, ensuring a just and effective energy transition in the United States.